Export potential of Indian agriculture Bihar-Perspective and issues - Prasad, Jagdish (Ed) (New Delhi Mittal, 2000)
In this book an attempt is made to ponder over the issues of export pontential of Indian agriculture with special reference to Bihar. The twenty one papers in this volume critically examine the pros and cons of export potential of Bihar agriculture giving
Keywords: Agriculture-India; Agriculture and state; International trade; Bihar(India)-Commerce; Horticultural product